STUDENTS’ GRAMMATICAL ERRORS IN TRANSLATING INDONESIAN SENTENCES INTO ENGLISH - Imansyah, Imansyah; Rarasani, Fedrilla (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The objectives of this research were to find out the types of students’ grammatical error, the dominant type of students’ grammatical error, and the causes of students’ grammatical error in translating Indonesian sentences into English. It was a descriptive qualitative research. The subject of this research was the 11th grade Language students at SMAN 6 Mataram consisting of 29 students, and the samples of this research were the Indonesian sentences that had been translated into English and the answers of questionnaire by the 11th grade Language students at SMAN 6 Mataram. In collecting the data, translation test and questionnaire were employed.The result of translation test showed that students committed 100 errors in the form of omission, addition, missformation, and missordering. The most frequent error committed by students was omission (37 or 37%). The second most frequently committed error was missformation (33 or 33%), the error was addition (17 or 17%), and the least was missordering (13 or 13%). Based on the questionnaire, 38.7% students' error was caused by interlingual (their mother tongue or source language).